ANALISIS SISTIM PENGAWASAN DALAM KAITANNYA DENGAN KINERJA KEUANGAN PADA BANK NTT - Wehelmina Ndoen (Journal of Management Small and Medium Enterprises (SMEs), 2018)
The study aims to determine how the application of control systems in relation to the financialperformance of the Bank NTT. The results of the study show that in implementing internal control,Bank NTT has established a plan of organization, separation of authority and responsibility, and asystem of distribution of authority in each work procedure. Bank NTT controls the employees'placement, employees' career opportunities, and employees' rotation and movement. Bank auditsconducted by Bank NTT include financial audits, operational audits and management audits. Allthree audits have been carried out properly so that the Bank NTT increased business development.This increase is reflected in an increase in lending assets, third party funds and revenues. Thismakes Bank NTT in the category of "healthy" bank.Keywords: Internal control, Bank Audits, Financial Performance